2018
DOI: 10.1021/acs.jproteome.8b00148
|View full text |Cite
|
Sign up to set email alerts
|

Machine-Learning-Based Prediction of Cell-Penetrating Peptides and Their Uptake Efficiency with Improved Accuracy

Abstract: Cell-penetrating peptides (CPPs) can enter cells as a variety of biologically active conjugates and have various biomedical applications. To offset the cost and effort of designing novel CPPs in laboratories, computational methods are necessitated to identify candidate CPPs before in vitro experimental studies. We developed a two-layer prediction framework called machine-learning-based prediction of cell-penetrating peptides (MLCPPs). The first-layer predicts whether a given peptide is a CPP or non-CPP, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
140
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(140 citation statements)
references
References 64 publications
0
140
0
Order By: Relevance
“…Twenty‐eight clusters were obtained. Among each cluster, the variable with the smallest ratio of 1‐R (Manavalan et al., ) was selected as a representative variable. Results of principal component analysis were showed in Figure , where values of the 28 variables for the training set and test set as well as the validation set occupied similar chemical space and they were significantly different from each other, indicating that the effectiveness of variable selection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐eight clusters were obtained. Among each cluster, the variable with the smallest ratio of 1‐R (Manavalan et al., ) was selected as a representative variable. Results of principal component analysis were showed in Figure , where values of the 28 variables for the training set and test set as well as the validation set occupied similar chemical space and they were significantly different from each other, indicating that the effectiveness of variable selection.…”
Section: Resultsmentioning
confidence: 99%
“…First, methodological evaluation was carried out to identify appropriate methods. Specifically, eight machine learning algorithms (Ericksen et al, 2017;Friedman, 2002;Manavalan et al, 2018;Siramshetty, Chen, Devarakonda, & Preissner, 2018) including DT, kNN, SVM, RF, ERT, AdaBoost, GBT, and XGBoost were evaluated and comprehensively compared through an application case of discriminating ACC inhibitors from decoys. Then, machine learning methods and traditional structure-based drug discovery were organically combined to construct a robust strategy for the discovery of ACC inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…(3-5, 26-28) These previous predictors were mostly trained using physicochemical descriptors, with datasets obtained from non-standardized experiments and containing only canonical residues. (6,(29)(30)(31) Inclusion of chemically diverse unnatural moieties is challenging because such physicochemical descriptors may not be readily available. The ability to encode for unnatural residues, however, would greatly expand the chemical search space, and Peptide sequences are represented as row matrices comprised of residue fingerprints.…”
Section: Developing the Machine Learning Modelmentioning
confidence: 99%
“…Results from the compositional analyses suggested that integrating the amino acid preference information would be helpful for differentiating between DHSs and non-DHSs, and so, we used these as input features for ML methods to improve classification. The major advantage of ML methods is their ability to consider multiple features simultaneously, often capturing hidden relationships [16][17][18][19][20][21][22][23].…”
Section: Compositional Analysismentioning
confidence: 99%
“…In the second step of the previous section, we used three different ML-based methods instead of SVM, including, RF, ET, and k-NN. A detailed description of the development of prediction models using these methods was provided in our recent studies [21,23]. For each ML-based method, we generated 33 prediction models using different sets of features, including individual composition, hybrid models, and features based on FIS cut-off.…”
Section: Comparison Of Three Ml-based Models With the Svm-based Modelmentioning
confidence: 99%